Penggunaan Model Pembelajaran Inkuiri Terbimbing Dalam Pembelajaran Ips Untuk Meningkatkan Kepekaan Sosial Terhadap Lingkungan Siswa Madrasah Ibtidaiyah Di Lamongan - Kiky Chandra Silvia Anggraini (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2017)
Abstract: The low social sensitivity to the environment is one of the most frequent problems, as evidenced by the lack of awareness to dispose of garbage in the trash, taking care of plants and others. Schools as the main educator agents play a role in improving the social sensitivity of students through learning so that through the materials and appropriate learning meodel will be able to improve students' social sensitivity to the surrounding environment. This research is a quasi-experimental research using SPSS 17,00 in analyzing data. Based on the pretest and posttest results in the experimental class using the guided inquiry learning model is more effective for improving students' social sensitivity than the control class that carries out the pure inquiry learning model. Analysis with t test by conducting independent sample test, found t count equal to 3,99 with significance level 0,00 (sig <0,05), this means Ho refused and accept Ha. This study proves that if Ha is accepted which contains the implementation of guided inquiry learning model is greater than the use of pure inquiry model in improving social sensitivity of students in social studies subjects.Keyword: Model learning, Inquiry, Social Sensitivity